2010
DOI: 10.1515/znb-2010-1113
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, in vitro Antiproliferative and Anti-HIV Activity of New Derivatives of 2-Piperazino-1,3-benzo[d]thiazoles

Abstract: A series of N- {2-oxo-2-[4-(1,3-benzothiazol-2-yl)piperazin-1-yl]}-(het)arenecarboxamides 4a -l, sulfonamide derivatives 8a -i as well as benzothiazole-containing N 1 -(2-oxoethyl)-N 1 -arylthioureas 9a -c have been synthesized. Compounds 4a -l and 9a were evaluated, in vitro, for their antiproliferative activity against a large panel of human tumor-derived cell lines. Compounds 4l and 9a were the most potent analogs in this series, showing remarkable effects on human splenic B-lymphoblastoid cells (WIL-2NS) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The biological study of the synthesized 2‐piperazino‐1,3‐benzo[ d ]thiazoles derivative 100 demonstrating impressive effectiveness on human acute T‐lymphoblastic leukemia CCRF‐CEM and B‐lymphoblastic leukemia CCRF‐SB, and the CC 50 value for 102 in CCRF‐SB cell line is 7.3 μM and for compound 100 , CC 50 value is 2.3 μM. To sum up, the addition of a thiourea residue increased the activity of the derivatives of benzothiazoles when compared to other analogs [32] …”
Section: The Fourth Decade (2001–2010)mentioning
confidence: 93%
See 1 more Smart Citation
“…The biological study of the synthesized 2‐piperazino‐1,3‐benzo[ d ]thiazoles derivative 100 demonstrating impressive effectiveness on human acute T‐lymphoblastic leukemia CCRF‐CEM and B‐lymphoblastic leukemia CCRF‐SB, and the CC 50 value for 102 in CCRF‐SB cell line is 7.3 μM and for compound 100 , CC 50 value is 2.3 μM. To sum up, the addition of a thiourea residue increased the activity of the derivatives of benzothiazoles when compared to other analogs [32] …”
Section: The Fourth Decade (2001–2010)mentioning
confidence: 93%
“…To sum up, the addition of a thiourea residue increased the activity of the derivatives of benzothiazoles when compared to other analogs. [32] In the same year, an environment-friendly and operational route for the synthesis of The biological study of the library of fused benzothiazole derivatives revealed compound 107, which has a tert-butyl substitution at the para position, as the one having greater potency. For both cell lines, at 10 μM of 107 total cell death was observed.…”
Section: The Fourthmentioning
confidence: 99%
“…Great concern has been recently focused on the development of heterocyclic compound bearing 1,3-thiazole ring system, which has been identified as a central structural element of several biologically active natural products such as thiamine vitamin B, and pharmacologically active substances in a large number of drugs as antibacterial, 1,2 antifungal, 3,4 antiviral, [5][6][7] anti-inflammatory, 8,9 anticancer, [10][11][12][13][14] anti-HIV, [15][16][17] anti-oxidant 18,19 and analgesic drugs. 20,21 Both classical and non-classical synthetic methods approaches were used to synthesize thiazole derivatives.…”
Section: Introductionmentioning
confidence: 99%